Price discovery of index futures across markets - CAO, Jerry X. (Institutional Knowledge at Singapore Management University, 2016)
The trading of foreign index futures by the Singapore Exchange (SGX) offers an ideal opportunity to study price discovery and information of trading across different markets. We examine four popular indices - Nikkei 225 Index, MSCI Taiwan Index, CNX Nifty Index and the FTSE China A50 Index traded in SGX and compare them with their home market trading. In contrary to standard theory and evidence, we show that smaller bid-ask spread, lower minimum lots and cheaper transaction cost do not necessary improve information efficiency. These results may shed some light on the usefulness of the role of an international financial centre on the price discovery of foreign indices.